Discrimination and Exploitation through On-the-Job Training and Hiring: The Case of the “Non-Elite” Seafarers in the Filipino Maritime Industry - Moran, Dawn (Philippine Journal of Labor and Industrial Relations, 2023)
This paper examines and exposes the discriminatory and exploitative practices prevalent in the recruitment and placement of “non-elite” cadets and graduates in the Filipino maritime industry. Non-elites are disadvantaged maritime cadets and graduates who did not make the cut for choice maritime schools that have partnerships with shipping companies. The findings show that non-elite cadets from the provinces, without backers, or lacking in “work experience” are more likely to work as “utility” workers in manning offices, as well as to pay placement/reservation fees to secure their shipboard training placements onboard. As utility workers, they are exploited to provide administrative (i.e., paperwork) or miscellaneous support (i.e., run personal errands for supervisor, or prepare coffee and buy snacks for the staff) for a pittance or none, and without any assurance on the length of service or the date of departure for their onboard training. Additionally, this involuntary servitude negatively lengthens their status as cadets, stunts their skills and competencies, and provides inaccurate academic rating of their competencies. Because of ship shortages for actual training onboard, lack of finances to enroll in the curriculum, or large numbers of cadets vying for a position onboard, cases of shipboard training being held in offices emerged during the survey and interviews. Findings also show that non-elite graduates with shipboard training in of􀏐ices and without backers have fewer employment opportunities. Likewise, they are exploited by manning agencies through requirement to provide utility services or attend unnecessary trainings. The study used a combination of quantitative survey, by simple random sampling, and qualitative key-informant interviews to support the statement that some shipboard training and employment placement practices contribute to the exploitation and discrimination of non-elite seafarers.